Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1038/jid.2014.373
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Melanoma Growth by a Non-Cardioselective β-Blocker

Abstract: Recently, retrospective studies provided conflicting results on the benefit of β-adrenoceptor-blockers (β-blockers) on melanoma progression. Most of these studies did not define the β-blocker used, making it difficult to understand the source of discrepancies between results. Therefore, we investigated the effect of non-cardioselective and cardioselective β-blockers on melanoma progression at the cellular, molecular, and tumor levels. Here we show that the non-cardioselective β-blocker propranolol hydrochlorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 28 publications
9
53
0
Order By: Relevance
“…Inhibiting β-adrenergic signaling to pancreatic cancer cells induced apoptosis by suppressing the Ras/Akt/ NFκB signaling pathway [47,48]. Similar findings were also reported in studies of hemangioma, neuroblastoma, melanoma and gastric cancer [49][50][51][52]. Chang et al go as far as to support the use of β-blockers as a possible novel therapeutic intervention, but that claim must be utilized with caution, as recent studies by Wang et al stated that B2 adrenergic stimulation with norepinephrine has actually attenuated invasion of certain types of breast CA's migration [53].…”
Section: Blood Transfusionsupporting
confidence: 70%
“…Inhibiting β-adrenergic signaling to pancreatic cancer cells induced apoptosis by suppressing the Ras/Akt/ NFκB signaling pathway [47,48]. Similar findings were also reported in studies of hemangioma, neuroblastoma, melanoma and gastric cancer [49][50][51][52]. Chang et al go as far as to support the use of β-blockers as a possible novel therapeutic intervention, but that claim must be utilized with caution, as recent studies by Wang et al stated that B2 adrenergic stimulation with norepinephrine has actually attenuated invasion of certain types of breast CA's migration [53].…”
Section: Blood Transfusionsupporting
confidence: 70%
“…PRO, at a concentration of 10 μM, with and without exogenous norepinephrine, significantly reduced proliferation (P < 0.001) and increased apoptosis (P < 0.01) of B16F10 cells compared to controls. Wrobel and Le Gal also showed that PRO had significant effects on proliferation and apoptosis in vitro on a panel of melanoma cell lines at a high concentration of 100 μM [35]. In vivo experiments using both primary and metastatic human melanoma tumours transplanted into immunodeficient (Nod SCID Gamma) mice showed that PRO at an average dose of 1.7 mg/day, tumour volumes were significantly lower (P < 0.001) than in untreated controls.…”
Section: Pre-clinical Evidence In Cancer - In Vitro and In Vivomentioning
confidence: 99%
“…For instance, propranolol, a non-selective β1/2-AR antagonist, reduces melanoma cell proliferation in human and murine melanoma cell lines (Wrobel and Le Gal 2015;Dal Monte et al, 2013). In addition, propranolol reduces tumor growth in a murine model of B16 melanoma (Hasegawa and Saiki 2002;Glasner et al 2010; Barbieri et al 2012).…”
Section: Introductionmentioning
confidence: 98%